Assesment of recombinant lines of maize hybrids for inbred development (Bangladesh Journal of Botany, 2015)
Maize (Zea mays L.) breeders currently exploit genetically narrow-base populations by deriving the recombination lines from F2 of commercial single cross hybrids. A mating design was proposed for maize hybrid evaluation as source germplasm. The commercial single cross hybrids, Hi Shell, DKC 7074 and PMZ 4, developed by the commercial company, Monsanto, were evaluated for their usefulness as germplasm. According to mating design three criteria were used: the percentage of inbreeding depression, the general combining ability and the specific combining ability. PMZ 4 had a lower percentage (21.9) of inbreeding depression, which was also combined with positive general combining ability (7.5) and negative specific combining ability. The estimated percentage of inbreeding depression was greater in DKC 7074 (31.4) and in Hi Shell (25.3). DKC 7074 also had negative general combining ability (35.5), while Hi Shell had positive specific combining ability (75.0). Therefore, evaluation through mating design showed PMZ 4 possesses more desirable genes and that its F2 may be a more profitable germplasm for developing elite inbred lines DOI: http://dx.doi.org/10.3329/bjb.v43i3.21615 Bangladesh J. Bot. 43(3): 363-366, 2014 (December)